(untitled) (Scientific journal of the Fergana State University, 2024)
The article examines the theoretical basis of improving the didactic support of the modernization of environmental education in the higher education system, the system and effectiveness of the improvement of the modernized didactic support of environmental education. Also, model of improvement of modernized didactic provision of environmental education in the higher education system were analyzed.